Contributions of sports as an strategy to reduce academic stress in university students: a systematic review (Jóvenes en la Ciencia, 2026)
Academic stress is the physiological response generated by an external stimulus that occurs in the educational context. This can result from the various tasks to be completed during a bachelor's degree, projects, exams. Regular physical activity, as well as participation in sports activities, can improve the emotional well-being of the student as well as their physical health. This paper aims to raise awareness among university students about physical activity as a tool to help reduce academic stress, and also to motivate students to engage in recreational spaces. After the research, the results showed that engaging in physical activity does indeed have a positive impact on mental health, helping to reduce high levels of stress.